A Study on the Talent Training Program for Inclusive Early Childhood Education — Taking Province G in China as an Example - Qiuhong Chao (Research and Advances in Education, 2024)
Early childhood education is the foundation of basic education, and inclusive early childhood education is an important part of China’s education system. The training and quality of teachers in early childhood education are key to ensuring “efforts to ensure that every child can enjoy fair and quality education.” The training program for early childhood education professionals is a guiding document for the standard and quality of teacher training, the organization of educational teaching, the implementation of the training process, and the certification of student graduation qualifications. A good training program promotes universities to cultivate high-quality professional and innovative teachers, which is beneficial to the development of high-quality inclusive early childhood education. Analyzing 14 texts of training programs for early childhood education teacher education majors in universities, we found that in terms of training objectives, the talent training objectives for “integration education literacy” lack accurate training positioning and characteristics. The setting of inclusive education courses is unreasonable, with an insufficient number of courses, mainly elective courses, few required courses, a narrow range of course offerings, and a teaching format that is more theoretical than practical. The course offering time is relatively concentrated and late, the assessment methods are mainly based on examinations, and the assessment methods are single. Therefore, universities should adjust the talent training objectives, offer a reasonable structure, scope, quantity, and duration of inclusive education courses, improve the course assessment methods, and ensure high-quality pre-service training for inclusive early childhood education teachers.